Investigation of support structure configurations for selective laser melting of In718 - Yi Nie; Chenlong Xu; Zhongkui Liu; Lihang Yang; Tianqi Li; Yinfeng He (Alexandria Engineering Journal)
The Selective Laser Melting (SLM), as a widely used metallic Additive manufacturing (AM) process, relies heavily on support structures. This study investigated the impact of different support structure configurations on the quality of In718 samples fabricated through SLM. On the basis of a comprehensive review of existing support structures configurations from the literature, three typical configurations: block, cone, and lattice, were designed to support cantilever parts for performance comparison. A coupled thermo-structural finite element simulation using ANSYS was performed to evaluate the temperature, deformation, and thermal stress evolution during the printing process of the three supported cantilever structures. The residual stress and deformation of the printed In718 cantilevers with different support structures were measured for validation. The results showed that block support exhibits the best strength and heat dissipation capability, making it the most effective support configuration for the SLM of In718 material. This research provides a fundamental procedure for evaluating the supporting performances among various support structures for the SLM process.